UiTM Global News : Engaging the world (Vol.3 / December 2019) - UiTM, Office of International Affairs (Office of International Affairs, 2019)
A quarterly newsletter showcasing UiTM's Internationalisation activities with the motto "Engaging the World." It features the engagement of UiTM with its partners at the global level.